Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Grave marker of Rosa Langston Watkins (7/5/1901-4/20/1973); Wife of Amos Watkins Chattanooga Memorial Park